2011
DOI: 10.1186/1472-6904-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug safety of rosiglitazone and pioglitazone in France: a study using the French PharmacoVigilance database

Abstract: BackgroundThiazolidinediones (TZDs), rosiglitazone (RGZ) and pioglitazone (PGZ) are widely used as hypoglycemic drugs in patients with type 2 diabetes mellitus. The aim of our study was to investigate the profile of adverse drug reactions (ADRs) related to TZDs and to investigate potential risk factors of these ADRs.MethodsType 2 diabetic patients were identified from the French Database of PharmacoVigilance (FPVD) between 2002 and 2006. We investigated ADR related to TZD, focusing on 4 ADR: edema, heart failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Regarding glitazones, these compounds have been associated with a higher risk of developing stroke, heart failure and all-cause mortality [ 14 17 ]. These excess risks were largest in people aged 65 years or older, and especially in patients treated with rosiglitazone [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…Regarding glitazones, these compounds have been associated with a higher risk of developing stroke, heart failure and all-cause mortality [ 14 17 ]. These excess risks were largest in people aged 65 years or older, and especially in patients treated with rosiglitazone [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…A meta-analysis of clinical trials conducted by Nissen and Wolski [106] in 2007 suggested that the use of rosiglitazone was associated with a significant increase in the risk of myocardial infarction. This led to rosiglitazone’s withdrawal from the European market in 2010 and a rosiglitazone black-box warning in the U.S. [105,107]. In 2013, the FDA lifted some prescription restrictions in the U.S. market based on a reevaluation of the Rosiglitazone Evaluated for Cardiac Outcomes and Regulation of Glycaemia in Diabetes (RECORD) trial (ClinicalTrials.gov Identifier NCT00379769) [108], but the European suspension is still in effect at the time of this writing.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of TZD-induced edema depends on drug dose, the stage of glucose intolerance, and the magnitude of the underlying cardiovascular disease. The lowest incidence is in prediabetes (DREAM study), with intermediate incidence in T2D (ADOPT and French PharmacoVigilance studies), and the highest in those with advanced cardiovascular disease (PROactive and IRIS studies) [31•, 34, 64••, 65••, 66•]. The extent to which TZD use exacerbates fluid retention in congestive heart failure is unclear [67].…”
Section: Thiazolidinediones: Fluid Retention and Edemamentioning
confidence: 99%